Computer assisted and robotic endoscopy and clinical image-based procedures : 4th International Workshop, CARE 2017, and 6th International Workshop, CLIP 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, proceedings /: 4th International Workshop, CARE 2017, and 6th International Workshop, CLIP 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, proceedings. (2017) - Unknown
No abstract available